A simplified conjugation scheme for lower semi-continuous functions. (2nd April 2016) - Elias, Leonardo M.; Martínez-Legaz, Juan E.
Abstract : We present two generalized conjugation schemes for lower semi-continuous functions defined on a real Banach space whose norm is Fréchet differentiable off the origin, and sketch their applications to optimization duality theory. Both approaches are based upon a new characterization of lower semi-continuous functions as pointwise suprema of a special class of continuous functions.